Which infrastructure can I use to share human neuroimaging data? A survey and literature review on current solutions for EU researchers - Lefort-Besnard, Jérémy; Pron, Alexandre; Clement, Patricia; Barker, Gareth; Erez, Yaara; Fernández-Seara, Maria A.; Feyzioglu, Saide Begüm; Hartman, Shir; Iglesias-Rey, Ramón; Keil, Vera; Mitrović, Tatjana; Nechifor, Ruben Emanuel; et al. (Aperture Neuro, 2025)
The ability to share research data publicly is crucial for enhancing statistical power, improving the quality of results, and ensuring the generalizability of findings. Despite the widespread availability of web-based tools and collaborative opportunities, sharing human neuroimaging data remains challenging for researchers based in the European Union (EU) due to various obstacles. In particular, many of the infrastructures available to share brain imaging data do not comply with the General Data Protection Rule (GDPR), which is applicable in the EU for all data that come from human participants. To investigate the awareness and utilization of data sharing platforms, we conducted a global survey targeting neuroimaging researchers. Our findings showed that amongst the 81 respondents, less than 50% were familiar with an infrastructure designed for EU researchers and about 20% had already shared data. Respondents also identified several key challenges, including legal compliance and privacy concerns, resource and infrastructure limitations, ethical considerations, institutional barriers, and awareness gaps. These results underscore the critical need to better publicize data sharing platforms that may be used by EU researchers. Here, we compiled a comprehensive list of infrastructures suitable for EU researchers to share brain imaging datasets from human participants.